PENGARUH PENDAPATAN, SANKSI DENDA, PELAYANAN FISKUS, DAN KESADARAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (Students' Journal of Accounting and Banking, 2012)
The population in this study are all taxpayer to land and building tax in the district of village Muktiharjo Kidul district of West Pedurungan Semarang regency in 2011 amounted 30.894 taxpayers. The sampling technique used is proportional stratified random sampling. The number of sample of 109 respondents. Data obtained through primary data by distributing questionnaires and secondary data obtained from the office of the district of village Muktiharjo Kidul district of West Pedurungan. Analysis of data using multiple linear regression analysis.The results showed test of the income variable has positive and significantly affect taxpayer compliance, did not taxpayer attitudes on sanction againts tax fine has positive and significant impact on taxpayer compliance, service tax authorities has positive and signifikan,taxpayer attitudes toward taxation awareness has positive and significant impact on taxpayer compliance. Simultane ously income, the taxpayer attitudes on fine sanctions and taxation awareness affect taxpayer compliance by 71,3%.Keywords: Taxpayer compliance, income, fine sanction, service tax authorities taxation awareness